Characteristics of Static Balance Function in Elderly Patients with Type 2 Diabetes Mellitus in Different Blood Pressure States - Shuai GUO; Zhizhen LIU; Jiawei QIN; Lianhua YIN; Jia HUANG; Jing TAO (康复学报)
Objective:To analyze the changes characteristics of static balance function in elderly patients with type 2 diabetes mellitus (T2DM) in different blood pressure states.Methods:A total of 2 179 medical records of eligible subjects who were selected for physical examination in the Second People's Hospital of Fujian University of Traditional Chinese Medicine from November 2013 to August 2020, which were divided into health people (the control group), the type 2 diabetes mellitus group under normal blood pressure state (T2DM group), the type 2 diabetes mellitus group under hypertension state (T2DM-HTN group) according to the state of blood pressure and blood sugar status, with 281 cases in the control group by the propensity score matching method, with 273 cases and 281 cases respectively in the T2DM group and the T2DM-HTN group. Compared the difference of blood biochemical indicators in three groups, such as fasting blood glucose (FBG), glycosylated hemoglobin (GHbA1c), triglycerides (TG), total cholesterol (TC), high/low density lipoprotein (HDL/LDL), etc.; compared the difference of health-related indicators in three groups, such as blood pressure (BP) and pulse rate per minute; compared the difference of static balance function parameters in three groups, such as track length (LNG), surface of the statokine-sigram (SSKG), LNG/area, track length-X(LNG-X), track length-Y(LNG-Y), romberg quotient (RQ) and deviation amplitude (DA).Results:①Blood biochemical indexes: compared with the control group, FBG, GHbA1c, TG, TC and LDL in the T2DM group and T2DM-HTN group were higher (P< 0.05); compared with T2DM group, FBG in the T2DM-HTN group was higher (P< 0.05). ②Health-related indicators: compared with the control group, BMI, pulse rate per minute and systolic and diastolic blood pressure in the T2DM group and T2DM-HTN group were higher (P< 0.05); compared with the T2DM group, BMI, pulse rate per minute and systolic and diastolic blood pressure in the T2DM-HTN group were higher (P< 0.05). ③Static balance function parameters: At open eyes state, compared with the control group, LNG/area in the T2DM group was higher (P< 0.05), LNG, SSKG, LNG/area, LNG-X and LNG-Y in the T2DM group were higher (P< 0.05); Compared with the T2DM group, LNG, LNG/area, LNG-X and LNG-Y in the T2DM-HTN group were higher (P< 0.05). At closed eyes state, compared with the control group, SSKG, LNG-X in the T2DM group were higher, LNG, SSKG, LNG-X, LNG-Y in the T2DM-HTN group were higher (P< 0.05); compared with the T2DM group, LNG, SSKG, LNG-X, LNG-Y in the T2DM-HTN group were higher (P< 0.05). Compared with the control group and the T2DM group, RQ and DA in the T2DM-HTN group were higher (P< 0.05).Conclusion:The ability of elderly patients with T2DM to maintain static postural was lower than that in non-diabetic patients of the same age, the patients with T2DM should provide more visual compensation to maintain stability, the balance control ability in the X-axis direction was more obviously affected by vision. Hypertension will lead to a further decline of the static balance ability of elderly patients with T2DM, and the offset amplitude of body center of gravity was greater.